IMPLEMENTATION OF A BUSINESS INCUBATOR IN THE FACULTY OF AGRO INDUSTRIAL ENGINEERING UNMSM. - Quispe Atúncar, Carlos (1998)
The Project will have the scope to the entire territory of Peru, in the natural regions: coast, mountain and forest. The beneficiaries of this project; entrepreneurs of Micro and Small Enterprises (MSEs), located in the main population centers of the country constitute 94% of the production centers of the country and contribute only 20% of the share of national GDP. Farmers also benefit from this project, just to maintain production to meet local demand and a scenario of poor promotion of new crops and limited expansion of the agricultural frontier.